2019
DOI: 10.1002/eem2.12051
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of Photocatalysis with Metal–Organic Frameworks

Abstract: Metal–organic frameworks (MOFs) as photocatalysts and photocatalyst supports combine several advantages of homogeneous and heterogeneous catalyses, including stability, post‐reaction separation, catalyst reusability, and tunability, and they have been intensively studied for photocatalytic applications. There are several reviews that focus mainly or even entirely on experimental work. The present review is intended to complement those reviews by focusing on computational work that can provide a further underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 215 publications
0
69
0
Order By: Relevance
“…Since other studies show that the inclusion of the dispersive Van der Waals forces improves the en-ergy description of the system [72], we have employed the method of Grimme, DFT-D3 [73]. To compute the acceptable bandgap energy con-sistent with the experiment, the PBE0 [74] hybrid functional was employed, which is implemented in the VASP code, as the literature has already shown that this functional predicts more accurate band gaps for Metal-Organic Frameworks (MOFs) [75]. Since the most stable surface of CuS nanoparticles is the CuS(001) with Cu/S termination, which is the dominant surface observed on hexagonal-shaped CuS nanoparticles [76], we have investigated the interaction of the CuS (1) surface with NH2-MIL-110(Cr).…”
Section: Density Functional Theory (Dft) Methodologymentioning
confidence: 99%
“…Since other studies show that the inclusion of the dispersive Van der Waals forces improves the en-ergy description of the system [72], we have employed the method of Grimme, DFT-D3 [73]. To compute the acceptable bandgap energy con-sistent with the experiment, the PBE0 [74] hybrid functional was employed, which is implemented in the VASP code, as the literature has already shown that this functional predicts more accurate band gaps for Metal-Organic Frameworks (MOFs) [75]. Since the most stable surface of CuS nanoparticles is the CuS(001) with Cu/S termination, which is the dominant surface observed on hexagonal-shaped CuS nanoparticles [76], we have investigated the interaction of the CuS (1) surface with NH2-MIL-110(Cr).…”
Section: Density Functional Theory (Dft) Methodologymentioning
confidence: 99%
“…and an ensuing computational study by Wu, Gagliardi, and Truhlar, who showed that charge separation can be established through the low‐lying empty orbitals of Ce 4+ , and only Ce 4+ from a set of metal ions also including Zr 4+ , Hf 4+ , Th 4+ , Ti 4+ , and U 4+ [45] . This approach has led to the development of UiO‐66(Ce) as photocatalysts for a multitude of reactions [105, 106] . Ce's empty orbitals were purposefully used as part of a MOF‐76 photocatalyst as well, [107] and recent times have seen a development of lanthanide‐based MOF photocatalysts [108]…”
Section: Challenges For Theorymentioning
confidence: 99%
“…[45] This approach has led to the development of UiO-66(Ce) as photocatalysts for amultitude of reactions. [105,106] Cesempty orbitals were purposefully used as part of aM OF-76 photocatalyst as well, [107] and recent times have seen ad evelopment of lanthanide-based MOF photocatalysts. [108] Another study,b yS ygantszeva et al,c ombined theory with experiment to show how ar ationale-based method to metal substitution can give control over band gap and band alignment.…”
Section: Bridging the Gap With Experimentsmentioning
confidence: 99%